Letter to Jane Tolmach from D.L. Commons - D.L. Commons:::::: (1976)
In a June 23, 1976 letter on Natomas Company stationery, President D. L. Commons offers belated congratulations to Jane Tolmach on winning the Democratic primary. He expresses confidence, based on his sources, that she is likely to win the general election and says he will be pleased to hear of her victory.